UMP alumnus Aidisyahrul is now a Robotics Engineer - Siti Nurfarmy, Ibrahim (2023)
PEKAN, 13 March 2023 – Having been interested in robotics since childhood and having the opportunity to participate in a robotics competition when representing the district level at the age of 11 encouraged Aidisyahrul Hanif, 24, to continue to explore this field while studying at Universiti Malaysia Pahang (UMP).